2016
DOI: 10.1016/j.biomaterials.2016.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of enteric neural progenitors with 5-HT4 agonist-loaded nanoparticles and thermosensitive hydrogel enhances cell proliferation and differentiation following transplantation in vivo

Abstract: Cell therapy offers an innovative approach for treating enteric neuropathies. Postnatal gut-derived enteric neural stem/progenitor cells (ENSCs) represent a potential autologous source, but have a limited capacity for proliferation and neuronal differentiation. Since serotonin (5-HT) promotes enteric neuronal growth during embryonic development, we hypothesized that serotonin receptor agonism would augment growth of neurons from transplanted ENSCs. Postnatal ENSCs were isolated from 2-4 week-old mouse colon an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 63 publications
0
37
0
Order By: Relevance
“…With approval from the Institutional Animal Care and Use Committee, neurospheres were generated from male and female 3-week old C57BL/6 mice (Jackson Labs, Bar Harbor, ME) according to previously published protocols (7, 12). The muscularis propria, which contains the myenteric plexus, was isolated from SI (duodenum through ileum; Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…With approval from the Institutional Animal Care and Use Committee, neurospheres were generated from male and female 3-week old C57BL/6 mice (Jackson Labs, Bar Harbor, ME) according to previously published protocols (7, 12). The muscularis propria, which contains the myenteric plexus, was isolated from SI (duodenum through ileum; Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Tissue preparation and immunohistochemistry were performed as previously described (7). Cells and tissues were fixed in 4% paraformaldehyde.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5-HT 4 signaling directly impacts postnatal gut-derived enteric neural stem/progenitor cell (ENSCs) proliferation as well. Neuronal proliferation and neuronal differentiation increase significantly in postnatal ENSCs and colon explants cultured with 5-HT 4 receptor agonist (RS67506)-loaded liposomal nanoparticles (Hotta et al 2016). Results are mimicked in vivo as co-transplantation of ENSCs with 5-HT4 receptor agonist-loaded nanoparticles leads to significantly increased neuronal density and proliferation (Hotta et al 2016).…”
Section: 5-ht and Neurogenesismentioning
confidence: 99%
“…Formation of NLBs from dissociated gut cells is now a common method to isolate and study enteric neural progenitors . However, a recent study showed that not all NLBs of cells that form in cultures of dissociated gut cells contain neural stem cells and not all NLBs give rise to neural derivatives under differentiation conditions .…”
Section: Isolation and Transplantation Of Enteric Neural Stem Cells Fmentioning
confidence: 99%